Experiment study on etching process of graphite electrode by DC hydrogen plasma. Issue 7 (24th February 2020) - Long, Lin; Zhou, Weixing; Tang, Jingfeng; Zhou, Desheng
Abstract: DC (direct current) graphite electrodes were used to investigate the hydrogen plasma etching characteristics. Results show that the intermittent spark is marked by physical etching, whereas glow discharge is marked by chemical etching. CH4 is the main gas product, together with the existence of C2 H6, C2 H4, C3 H8, and C3 H6 . A detailed analysis of the 20‐mA glow discharge showed that the chemical reactions due to the plasma occur mainly through hydrogenation reactions on graphite defects, and different plasma action zones on the graphite also play different roles. Additionally, plasma gaseous reaction processes were analyzed through free radical reactions. Abstract : Graphite electrodes in different hydrogen plasma reaction regions in the electrostatic field have a different etching status. CH4 is the main gas product of glow discharge, together with the other hydrocarbon gas products. The whole etching process of graphite by plasma is analyzed in detail, especially the process of hydrogenation on graphite surfaces and gaseous free radical reactions